Low pre-transplant levels of mannose-binding lectin are associated with viral infections and mortality after haematopoietic allogeneic stem cell transplantation - Puente, M. (BMC Immunol, 2019)
BACKGROUND: Mannose-binding lectin (MBL) is a key component of innate immunity. Low serum MBL levels, related to promoter polymorphism and structural variants, have been associated with an increased risk of infection. The aim of this work was to analyse the incidence and severity of infections and mortality in relation to the MBL2 genotype and MBL levels in patients underwent allogeneic haematopoietic stem cell transplantation (Allo-HSCT). RESULTS: This was a prospective cohort study of 72 consecutive patients underwent Allo-HSCT between January 2007 and June 2009 in a tertiary referral centre. Three periods were considered in the patients’ follow-up: the early period (0–30 days after Allo-HSCT), the intermediate period (30–100 days after Allo-HSCT) and the late period (> 100 days after Allo-HSCT). A commercial line probe assay for MBL2 genotyping and an ELISA Kit were used to measure MBL levels. A total of 220 episodes of infection were collected in the 72 patients. No association between donor or recipient MBL2 genotype and infection was found. The first episode of infection presented earlier in patients with pre-transplant MBL levels of < 1000 ng/ml (median 6d vs 8d, p = 0.036). MBL levels < 1000 ng/ml in the pre-transplant period (risk ratio (RR) 2.48, 95% CI 1.00–6.13), neutropenic period (0–30 days, RR 3.28, 95% CI 1.53–7.06) and intermediate period (30–100 days, RR 2.37, 95% CI 1.15–4.90) were associated with increased risk of virus infection. No association with bacterial or fungal disease was found. Mortality was associated with pre-transplant MBL levels < 1000 ng/ml (hazard ratio 5.55, 95% CI 1.17–26.30, p = 0.03) but not with MBL2 genotype. CONCLUSIONS: Patients who underwent Allo-HSCT with low pre-transplant MBL levels presented the first episode of infection earlier and had an increased risk of viral infections and mortality in the first 6 months post-transplant. Thus, pre-transplant MBL levels would be important in predicting susceptibility to viral infections and mortality and might be considered a biomarker to be included in the pre-transplantation risk assessment.